The complete mitochondrial genome of Palomena viridissima (Hemiptera: Pentatomidae) and phylogenetic analysis - Chen, Wen-Ting (Mitochondrial DNA B Resour, 2021)
Here, we sequenced and annotated the complete mitochondrial genome (mitogenome) of Palomena viridissima (Hemiptera: Pentatomidae). This mitogenome was 15,118 bp long, comprising of 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rrnL and rrnS) and a large non-coding control region. The P. viridissima mitogenome with an A + T content of 76.0%, presented a positive AT-skew (0.11) and a negative GC-skew (-0.13). Ten PCGs started with a typical ATN codon, two PCGs started with TTG (atp8, nad1), whereas the remaining one used AAC (cox1). All tRNAs had a typical secondary cloverleaf structure, except for trnS1 which lacked the dihydrouridine arm. The Bayesian phylogenetic analysis based on mitogenomic data supported a sister relationship of P. viridissima and Nezara viridula from the same tribe Nezarini and recovered a phylogeny of Pentatominae: (Menidini + (Strachiini + (Pentatomini + ((Cappaeini + Halyini) + (Eysarcorini + (Nezarini + Carpocori)))))).